1987
DOI: 10.1212/wnl.37.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic complications after gastric restriction surgery for morbid obesity

Abstract: We report the occurrence of neurologic complications in 23 patients who underwent gastric restriction surgery for the treatment of morbid obesity. Complications occurred 3 to 20 months after surgery. All the patients had had protracted vomiting for the first 3 months after the operation. The following syndromes were found: chronic or subacute symmetric polyneuropathy (12 patients), acute severe polyneuropathy (1 patient), burning feet syndrome (2 patients), meralgia paresthetica (3 patients), myotonic syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
0
10

Year Published

1994
1994
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(121 citation statements)
references
References 0 publications
2
109
0
10
Order By: Relevance
“…Bundan başka gastrointestinal cerrahi, kemoterapi, sistemik enfeksiyonlar, diyetteki yetmezlikler ve aşırı kusma gibi sekonder nedenler tiamin eksikliğine yol açar (6,9). Bariatrik cerrahi sonrası belirgin hale gelen nörolojik komplikasyonlar 3-20. aylarda olup, özellikle uzun süre kusması olan hastalarda daha sık görülür (10). Uzun süre bulantı, kusma yakınması olan hastamızın hemogram, biyokimya, troid fonksiyon testleri, folik asit ve B12 düzeyleri normal olmakla birlikte tiamin hastanemizde bakılamadığı için başka bir merkeze gönderildi.…”
Section: Discussionunclassified
“…Bundan başka gastrointestinal cerrahi, kemoterapi, sistemik enfeksiyonlar, diyetteki yetmezlikler ve aşırı kusma gibi sekonder nedenler tiamin eksikliğine yol açar (6,9). Bariatrik cerrahi sonrası belirgin hale gelen nörolojik komplikasyonlar 3-20. aylarda olup, özellikle uzun süre kusması olan hastalarda daha sık görülür (10). Uzun süre bulantı, kusma yakınması olan hastamızın hemogram, biyokimya, troid fonksiyon testleri, folik asit ve B12 düzeyleri normal olmakla birlikte tiamin hastanemizde bakılamadığı için başka bir merkeze gönderildi.…”
Section: Discussionunclassified
“…In an early series of 500 patients with BS, 0.4% patients developed WE. 34 Systemic reviews discussing WE after BS have reported finding in 32 and 84 cases. 35,36 More than 80% cases were women in both reviews with onset of symptoms between 2 weeks to 18 months of surgery.…”
Section: Neurologicalmentioning
confidence: 99%
“…The Swedish Obese Subjects study (2) clearly showed that weight loss following surgery sustained 10 years post-surgery, whereas non-surgical treatment modalities did not result in long-term weight loss. Despite high percentages of weight loss, bariatric surgeries have been shown to result in many adverse events including neuropathies (3,4).…”
Section: Introductionmentioning
confidence: 99%